2018
DOI: 10.1016/j.apsb.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Radiopaque nano and polymeric materials for atherosclerosis imaging, embolization and other catheterization procedures

Abstract: A review of radiopaque nano and polymeric materials for atherosclerosis imaging and catheterization procedures is presented in this paper. Cardiovascular diseases (CVDs) are the leading cause of death in the US with atherosclerosis as a significant contributor for mortality and morbidity. In this review paper, we discussed the physics of radiopacity and X-ray/CT, clinically used contrast agents, and the recent progress in the development of radiopaque imaging agents and devices for the diagnosis and treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 98 publications
0
24
0
Order By: Relevance
“…Atherosclerosis (AS), a leading cause of death worldwide, is a lipid-driven inflammatory disease 1 , 2 . AS is characterized by plaque buildup at the arterial subendothelial space (intima) due to the accumulation of diseased cells including monocytes, macrophages, endothelial cells, smooth muscle cells, neutrophils, lipids, and extracellular matrix components 3 , 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis (AS), a leading cause of death worldwide, is a lipid-driven inflammatory disease 1 , 2 . AS is characterized by plaque buildup at the arterial subendothelial space (intima) due to the accumulation of diseased cells including monocytes, macrophages, endothelial cells, smooth muscle cells, neutrophils, lipids, and extracellular matrix components 3 , 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, although polymeric devices can be detected by ultrasound technique after implantation in vivo, 29,30 computed tomography (CT) can present the size, shape, and composition of implanted device, which is important for postoperative analysis. 31,32 Thus, the development of radiopaque resorbable materials still remains as an urgent need for clinical use.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, we could further decrease the radiopaque agent content in our formulation and hence viscosity, without significantly altering the fluoroscopic visibility of the liquid precursor. Radiopaque nanoparticles might also improve injectability to an even greater extent (Tian et al, 2018) and allow a higher percentage of polymer, thereby potentially shortening the photosolidification process to a minute or less. It is known that iodinated contrast agents are subject to leak to the surrounding environment (Lei et al, 2016), as it was demonstrated for our hydrogel over the following days due to the immersion process ( Figure 6B).…”
Section: Discussionmentioning
confidence: 99%